EFFECTS OF COVID-19 PANDEMIC ON THE LOW-INCOME URBAN COMMUNITIES’ (B40) WELL-BEING: A CASE STUDY OF PPR HILIRAN AMPANG, MALAYSIA - Isa, Nor Kalsum Mohd; Yunos, Mohd Yazid Mohd; Isa, Nor Junainah Mohd; Ibrahim, Mohd Hairy; Alias, Anuar; Khairzaman, Norsuhaibah; Ismail, Mohd Sobri (CENTRAL ASIA AND THE CAUCASUS, 2021)
Coronavirus outbreak 2019 (COVID-19) and Movement Control Order (MCO) announced by the Government of Malaysia since mid-March 2020 have had significant implications for the movement of the population to carry out economic activities and activities to meet other daily needs. The low-income group especially in urban areas is a very vulnerable community that is experiencing some sudden lifestyle changes due to these MCOs and pandemics. The aim of this study is to compare the level of well-being of the low-income urban community (bottom 40 percent of income earners- B40) before and during the COVID-19 pandemic and evaluate the impact of the COVID-19 pandemic on the well-being of the B40 urban community throughout the pandemic. This case study is a quantitative study that focuses on the B40 urban community living in the housing area of the Hiliran Ampang People's Housing Program (PPR Hiliran Ampang). Two hundred seventy-four (274) heads of households were involved as a sample to fill in the questionnaire. The collected data were analyzed using the descriptive statistics (frequency, mean and percentage) and inference (t-test, Pearson Correlation and multiple regression analysis). The findings show that the level of well-being of the PPR Hiliran Ampang community is at a moderate level with a mean score of 3.93 before the pandemic. This level of well-being decreased with a mean value of 0.02, making the mean score throughout the pandemic 3.92. The COVID-19 pandemic resulted in a declining monthly income of households and the fact that the number of non-income households increased by 12 percent throughout the pandemic. Based on the multiple regression analysis, it shows that the total monthly household income affects the three domains of B40 urban community’s well-being, namely the well-being in family and community relationships, economic as well as family and community health.